Tactile Sensor on Cane Handle for Gait Phase Analysis. - De-Guzmán-Manzano, Arturo; Trujillo-León, Andrés; Lora Rivera, Raúl; Vidal-Verdú, Fernando (IEEE, 2019)
Low cost devices such as accelerometers, gyroscopes, or force sensing resistors have been exploited to build wearable systems for gait analysis. These sensors are sometimes mounted on a cane if it is required. This paper proposes the use of a tactile sensor on the cane handle to obtain information about gait phases. Moreover, since the sensor is located at the human-device interface, any shaping of the force at this interface that anticipates the movement can be registered. Experimental results from an instrumented cane are presented to illustrate this behavior that can be exploited in applications that involve closed loop control.
https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/#accepted
Keywords: Biomecánica; Biosensores; Prótesis; Ingeniería biomédica; Gait; Instrumented cane